2015
DOI: 10.1111/hae.12652
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and management of acute coronary syndromes among adult persons with haemophilia: results of an international, retrospective, 10‐year survey

Abstract: Sparse data are available on presentation and management of acute coronary syndromes (ACS), including unstable angina and non-ST- and ST-elevation myocardial infarction, among persons with haemophilia (PWH). The aim of this study was to determine demographics, bleeding disorder characteristics, cardiovascular risk factors (CRFs), interventions, haemostatic protocol, revascularization outcomes and complications among PWH with ACS. Members of an international consortium comprising >2000 adult PWH retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 23 publications
1
66
0
2
Order By: Relevance
“…The process of search and article selection is shown in Figure . Information for the present analysis was extracted from 29 articles (case reports and small case series) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of search and article selection is shown in Figure . Information for the present analysis was extracted from 29 articles (case reports and small case series) .…”
Section: Methodsmentioning
confidence: 99%
“…However, at least two patients (including the patient presented in the case report) experienced severe bleeding episodes months after PCI. Another patient with mild hemophilia A experienced excessive gastrointestinal bleeding during monotherapy with ASA requiring discontinuation [9].…”
Section: Bleeding Complications During and After Coronary Angiograpmentioning
confidence: 99%
“…However, recent guidelines and expert opinions [10,11,12,13,14,17] advocate that acute coronary disease in PWH should generally be managed as in non-PWH, provided that factor replacement is given, and they consider ASA therapy (with factor levels >5%) and dual anti-platelet therapy (with factor levels >15-30%) to be generally safe. This is supported by 2 recently published case series on 24 PWH with CVD [18,19], who found that revascularization and anti-platelet treatment were generally well-tolerated. The 2 cases of PCI and 4 cases of CABG reported in our population were all successful and without bleeding complications.…”
Section: Tablementioning
confidence: 53%
“…Leger med liten erfaring med pasienter med blødersykdom vil med stor sannsynlighet komme i kontakt med disse pasientene, som nå i større grad rammes av aldersrelaterte sykdommer på samme måte som resten av befolkningen. Videre forskning som gir grunnlag for utvikling av egne retningslinjer for behandling av pasienter med alvorlig blødersykdom, vil vaere viktig i fremtiden (13,14). Godt samarbeid mellom hematologer og leger i andre spesialiteter vil vaere viktig for å kunne gi bløderne best mulig behandling.…”
Section: Materiale Og Metodeunclassified